CO2 hydrogenation to liquid hydrocarbons via modified Fischer–Tropsch over alumina-supported cobalt catalysts: Effect of operating temperature, pressure and potassium loading. Issue 41 (October 2020) - Khangale, Phathutshedzo R.; Meijboom, Reinout; Jalama, Kalala
Highlights: TPR revealed that potassium limited the reduction of the catalyst. Potassium decreased the selectivity to methane. Potassium increased the selectivity to C2+ hydrocarbons. Maximum C2+ yield of 10.2% was obtained when 6 wt.% of potassium CO2 is first converted to CO via RWGSR, followed by subsequent hydrogenation of CO to HC Abstract: The effect of promoting 15%Co/Al2 O3 catalyst with potassium on CO2 hydrogenation to longer-chain hydrocarbons was investigated. The catalysts used in this study were synthesized using an incipient wetness impregnation of the support with nitrate solutions. All catalysts were supported on γ-alumina and promoted with potassium (0 – 8%). The synthesized catalysts were characterized by XRD, BET, XPS, TPR and CO2 -TPD analyses. The catalysts were evaluated for CO2 hydrogenation using a fixed-bed tube reactor. The CO2 conversion was found to increase with both the reaction temperature and pressure. The TPR data revealed that potassium limited the reduction of the catalyst, decreased the selectivity to methane and increased the selectivity to C2+ hydrocarbons. The maximum C2+ yield of 10.2%, with CO2 conversion of 42.3%, was obtained when 6 wt.% of potassium was added to the catalyst. It is believed that during the CO2 hydrogenation process over the catalysts that were promoted with potassium, CO2 is first converted to CO via reverse–water–gas–shift reaction, followed by subsequent hydrogenation of CO to hydrocarbons.